2019
DOI: 10.1039/c9ra02872b
|View full text |Cite
|
Sign up to set email alerts
|

Highly malleable haem-binding site of the haemoprotein HasA permits stable accommodation of bulky tetraphenylporphycenes

Abstract: Bulky metallo-tetraphenylporphycene was successfully incorporated into haemophore HasA which have flexible loops surrounding heme-binding site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Structurally, porphycenes consist of two 2,2′-bipyrrole subunits linked by two ethylene linkers resulting in a smaller and more rectangular N 4 cavity than porphyrin, which causes the porphycenes to exhibit a unique coordination site. In recent years, the exploration of new synthetic methods of porphycenes has received considerable attention due to the synthetic challenges in typical methods. The lack of efficient and economical synthetic methods for large scale porphycene production inhibited the growth of coordination chemistry of porphycene compared to that of its parent isomer, porphyrin. Indeed, homo- or heterobinuclear complexes of porphycenes are rare. , Against this background, we have recently succeeded in the large scale synthesis of porphycenes with a facile method . This progress encouraged us to investigate an extensive study of the coordination chemistry of porphycene.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, porphycenes consist of two 2,2′-bipyrrole subunits linked by two ethylene linkers resulting in a smaller and more rectangular N 4 cavity than porphyrin, which causes the porphycenes to exhibit a unique coordination site. In recent years, the exploration of new synthetic methods of porphycenes has received considerable attention due to the synthetic challenges in typical methods. The lack of efficient and economical synthetic methods for large scale porphycene production inhibited the growth of coordination chemistry of porphycene compared to that of its parent isomer, porphyrin. Indeed, homo- or heterobinuclear complexes of porphycenes are rare. , Against this background, we have recently succeeded in the large scale synthesis of porphycenes with a facile method . This progress encouraged us to investigate an extensive study of the coordination chemistry of porphycene.…”
Section: Introductionmentioning
confidence: 99%
“…1a), can accept various bulky synthetic metalloporphyrins, such as diphenylporphyrin. [34][35][36][37] Yet, at this time, we were unable to incorporate bulkier TPP into HasA and concluded that this may not be possible, 34,35 and that the TPP skeleton may be incompatible for incorporation into unadulterated proteins and application with natural biological systems.…”
mentioning
confidence: 87%
“…Recently, we have successfully expanded the scope of available synthetic metal complexes for heme substitution in the heme acquisition system protein A (HasAp) [16][17][18][19][20][21] which is a hemophore secreted by Pseudomonas aeruginosa under iron-decient conditions. [22][23][24][25] The crystal structure of the hemebinding form of HasA (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…25 Based on these HasA characteristics, we expected that HasAp could stably incorporate a plethora of synthetic metal complexes with structures that differ greatly from heme, and we succeeded in incorporating several synthetic metal complexes including iron(III)-tetraphenylporphyrin (Fe-TPP). [16][17][18][19][20][21] TPP has a highly symmetric and rigid skeleton, and a variety of TPP derivatives can be produced by using established synthetic methods. [26][27][28][29] These characteristics have been used in the design of synthetic supermolecules such as metal-organic frameworks 30,31 and caged metal complexes, 32,33 where they contribute to the control of the assembled structures.…”
Section: Introductionmentioning
confidence: 99%